Demographic Change, Generation Effects and Housing Markets: Homeownership as Pension? - Helbrecht, Ilse; Geilenkeuser, Tim (Raumforschung und Raumordnung | Spatial Research and Planning, 2012)
This article examines recent shifts among German homeowners towards the use of their housing equity under the circumstance of demographic change. Whilst traditionally housing equity was considered a consumer good, recent developments in pension provision and demographics strengthen its position as a pension asset. Consequently, more and more young German households consider their dwelling to be a centrepiece of their financial provisions in preparation for future risks and for retirement. This is clearly a new perspective in a predominantly tenant society. Based on 36 in-depth interviews with members of households, the authors assert that homeowning behaviour and attitudes have evolved differently for different generations and point out distinguishable “housing generations”. The younger a household the more often housing equity features as an investment good, with the downside that with this development continuing inheritances may decline, often the only way young German households can afford buying a house.
Keywords: Homeownership; Demographic change; Housing generation; Retirement strategies